Evaluation of Sustainable Tourism Development Planning in Dumai City - Anastasya, Beby; Apriliani, Indah; Regina, Nurmaisya; Erinaldi, Erinaldi (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to evaluate the effectiveness of sustainable tourism development planning in Dumai City by reviewing the suitability of regional policies to the principles of economic, social, and environmental sustainability. The research uses the Systematic Literature Review (SLR) approach by analyzing various latest scientific sources and empirical data from the 2024 Government Agency Performance Report (LKjIP) of the Dumai City Youth, Sports, and Tourism Office. The results of the study show that tourism development in Dumai City has made a positive contribution to increasing the number of tourists and regional income, with the achievement of 144.32% of the realization of visits and an increase in PAD of up to 185% of the target. However, the implementation of sustainability principles is still not optimal, especially in the aspects of community participation and environmental management. This weakness shows the need for collaborative governance as well as strengthening community-based ecotourism and creative economy programs. This study recommends that tourism planning in Dumai City be directed at the balanced integration of economic, social, and ecological dimensions through the implementation of sustainability indicators that are in line with the Sustainable Development Goals (SDGs). With this approach, tourism development in Dumai City is expected to take place in an adaptive, inclusive, and competitive manner in the long term.